Gel Properties and Formation Mechanism of Camellia Oil Body-Based Oleogel Improved by Camellia Saponin - Jing Liu; Lili Hu; Yaqing Xiao; Yingnan Liu; Songnan Li; Mingming Zheng; Zhenyu Yu; Kang Liu; Yibin Zhou (Gels, 2022)
This study aimed to investigate the effect of camellia saponin (CS) on the structural characteristics, texture properties, rheological properties, and thermal stability of camellia oil body-based oleogel (COBO). In addition, the formation mechanism of COBO was further studied in terms of the microstructure and texture of freeze-dried products, the mobility of hydrogen protons, and the conformation and structure changes of oleosin. The texture and rheological properties of the oleogels were found to be gradually improved with the incorporation of CS. This was attributed to the CS-induced enhancement of oil body interfacial film. CS was likely to bind to oleosin via hydrogen bonding and hydrophobic interactions, thereby forming a thick CS-oleosin complex interface, which was revealed by the oleosin fluorescence quenching and an increase in the ordered structure (α-helix). The composite interface could resist the crystallization damage and air disturbance caused by solidification and sublimation of water during freeze-drying, resulting in a denser and more uniform three-dimensional gel structure to trap the liquid oil, which could be explained by the decreased mobility of hydrogen protons in oleogel. The work offers a new proposal and theoretical basis for the development of saponin-enhanced oleogels using non-thermal processing.